Proton-Translocating Nicotinamide Nucleotide Transhydrogenase: A Structural Perspective - Zhang, Qinghai; Padayatti, Pius S.; Leung, Josephine H. (Frontiers in Physiology, 2017)
Nicotinamide nucleotide transhydrogenase (TH) is an enzyme complex in animal mitochondria and bacteria that utilizes the electrochemical proton gradient across membranes to drive the production of NADPH. The enzyme plays an important role in maintaining the redox balance of cells with implications in aging and a number of human diseases. TH exists as a homodimer with each protomer containing a proton-translocating transmembrane domain and two soluble nucleotide binding domains that mediate hydride transfer between NAD(H) and NADP(H). The three-domain architecture of TH is conserved across species but polypeptide composition differs substantially. The complex domain coupling mechanism of TH is not fully understood despite extensive biochemical and structural characterizations. Herein the progress is reviewed, focusing mainly on structural findings from 3D crystallization of isolated soluble domains and more recently of the transmembrane domain and the holo-enzyme from Thermus thermophilus. A structural perspective and impeding challenges in further elucidating the mechanism of TH are discussed.